Предмет: Алгебра,
автор: Batman123123
1) Упростить выражение а) (2x+1)(x-1)= б) a²+(2-a)(a+5)= 2) Разложить на множители а) xy+3y+xa+3a= б) a³-3ab-2a²b+6b²= 3) Решить уравнение (3-x)(x+4)+x²=0
Ответы
Автор ответа:
1
1)
а) (2x+1)(x-1) = 2x^2 -x -1
б) a^2 + (2-a)(a+5)= a^2 - a^2 - 3a + 10 = 10-3a
2)
а) xy + 3y + xa + 3a = y(x+3) + a(x+3) = (x+3)(y+a)
б) a^3 -3ab - 2a^2b + 6b^2 = a^2(a-2b) - 3b(a-2b) = (a-2b)(a^2 - 3b)
3) (3-x)(x+4) + x^2 = 0
-x^2 -x + 12 + x^2 = 0
-x+12=0
x = 12
а) (2x+1)(x-1) = 2x^2 -x -1
б) a^2 + (2-a)(a+5)= a^2 - a^2 - 3a + 10 = 10-3a
2)
а) xy + 3y + xa + 3a = y(x+3) + a(x+3) = (x+3)(y+a)
б) a^3 -3ab - 2a^2b + 6b^2 = a^2(a-2b) - 3b(a-2b) = (a-2b)(a^2 - 3b)
3) (3-x)(x+4) + x^2 = 0
-x^2 -x + 12 + x^2 = 0
-x+12=0
x = 12
Автор ответа:
1
Похожие вопросы
Предмет: Русский язык,
автор: Vovarickbro
Предмет: Русский язык,
автор: 573987640
Предмет: Математика,
автор: alena6v84we
Предмет: Алгебра,
автор: nastyaevgentom
Предмет: Химия,
автор: 12121212121212д